A method to transfer an individual graphene flake to a target position with a precision of sub-micrometer*Project supported by the National Key Research and Development Program of China (No. 2016YFB0402404), the High-Tech Research and Development Program of China (Nos. 2013AA031401, 2015AA016902, 2015AA016904), and the National Natural Foundation of China (Nos. 61674136, 61176053, 61274069, 61435002). (April 2017) - Wang, Yubing; Yin, Weihong; Han, Qin; Yang, Xiaohong; Ye, Han; Lü, Qianqian; Yin, Dongdong
Abstract: Graphene field-effect transistors have been intensively studied. However, in order to fabricate devices with more complicated structures, such as the integration with waveguide and other two-dimensional materials, we need to transfer the exfoliated graphene samples to a target position. Due to the small area of exfoliated graphene and its random distribution, the transfer method requires rather high precision. In this paper, we systematically study a method to selectively transfer mechanically exfoliated graphene samples to a target position with a precision of sub-micrometer. To characterize the doping level of this method, we transfer graphene flakes to pre-patterned metal electrodes, forming graphene field-effect transistors. The hole doping of graphene is calculated to be 2.16 × 10 12 cm − 2 . In addition, we fabricate a waveguide-integrated multilayer graphene photodetector to demonstrate the viability and accuracy of this method. A photocurrent as high as 0.4 μ A is obtained, corresponding to a photoresponsivity of 0.48 mA/W. The device performs uniformly in nine illumination cycles.